Alternative oxidase respiration in the mycorrhizal fungus Laccaria bicolor - Mikaelsson, Hilda (SLU/Dept. of Forest Ecology and Management, 2019)
The temperature on Earth is rising, and one of the main drivers is anthropogen-ic greenhouse gases such as carbon dioxide (CO2). The world’s forests act as carbon sinks, binding carbon into their biomass. The net carbon assimilation is determined by the uptake and release of CO2 through the processes of photo-synthesis and respiration. Respiration in plants and most fungi can proceed via two pathways. The most frequently used pathway ends with the terminal com-plex Cytochrome C oxidase (COX), but it can also follow a less efficient alter-native pathway, which ends with Alternative oxidase (AOX). The rate by which plants and other organisms use the alternative pathway affects their carbon use efficiency. Both enzymes use atmospheric oxygen as their substrate, but they discrimi-nate differently against the isotope 18O. In this study, the presence of AOX in the mycorrhizal fungus Laccaria bicolor was proven, using isotope ratio mass spectrometry (IRMS). Based on the 18O discrimination of the mycelium in the presence of pathway specific inhibitors, the electron partitioning to each path-way in untreated mycelium (i.e. without inhibitors) was estimated. As found in previous studies on plants, the discrimination was found to be affected by the water content of the sample. Since this effect was probably derived from diffusion limitation, all discrimination values were normalized to correspond to the mean water content, 94.4%. The 18O discrimination of L. bicolor was found to be 18.8±0.9, which is comparable to COX values previ-ously found in plants and to discrimination values of baker’s yeast, Saccar-omyces cerevisiae, which lacks AOX. This indicated that the use of AOX in young mycelium of L. bicolor was negligible. However, a correlation was dis-covered between AOX contribution and age, suggesting that AOX plays an increasingly important role in ageing mycelium. The oxygen isotope discrimination method is currently the only reliable way of measuring AOX/COX partitioning during respiration. However, despite numerous studies in various species, this is the first time it has been applied to fungal mycelium, and as such it represents an important step towards a greater understanding of fungal respiration. Further studies of fungal AOX under natu-ral conditions, in combination with estimations of fungal biomass, has a great potential to improve the accuracy of carbon sequestration models.